La lingua del possibile: il Metaverso - Matetich, Sara (Aesthetica Preprint, 2023)
The possibility of embodying social connectivity in a new world-form is being announced: it is called the Metaverse. The technology that promises the creation of this mixed world (opp. cross-world) is still being perfected, but the project that determines it has already been established: to increase the involvement of internet users, in order to give them the most satisfying immersiveness possible to fully enjoy the onlife experience, where “what is real is informational and what is informational is real” – as Luciano Floridi wrote, paraphrasing Hegel. Therefore, in addition to the continuous adaptation of a digital re-ontologization of the world, it is urgent to identify the peculiarities of the language, and of the relevant structure, on which the Metaverse envisages its own foundations. The following essay will deal with this, starting from Mark Zuckerberg’s recent promise of wanting to create a unique language, developed exclusively for the citizens of the Metaverse, thus realizing that ‘superpower’ that has always been coveted at all latitudes: universal communication! A promise of this kind is imbued with implications of an aesthetic nature: from the creation of a new linguistic community, which includes all the differences linked to the cultural context of reference, up to the literacy techniques that it will be necessary to initiate and investigate, in order to allow participants of the Metaverse experience to know how to use the new language to build – and settle in – their new world.